Helicobacter Pylori Related Gastric Cancer Screening and Cost-Effectiveness Analysis: A Hospital-Based Cross-Sectional Study (SIGES). - Xiang, Wen; Wang, Rui; Bai, Dan; Yu, Tian-Hang; Chen, Xin-Zu (Nutrition & Cancer, 2022)
To evaluate the effectiveness of Helicobacter pylori (Hp) related gastric cancer screening (Hp-GCS) and cost-effectiveness of protocol candidates in a hospital-based cross-sectional study. A total of 163 gastric cancer patients in West China Hospital were retrospectively collected according to ICD-10 code and histologic proof between April 1, 2013 and March 31, 2014, and 15,599 cancer-free controls were simultaneously collected from the health checkup registry. Hp infection was examined by urea breath test (UBT). The prevalence of Hp infection was compared between patients and controls. The diagnostic performance of UBT-based predictive index was tested in both training and validation settings. Cost-effectiveness analysis was conducted to assess candidates of Hp-GCS protocols. The prevalence of Hp infection was 55.8% and 41.2% in gastric cancers and controls, respectively (p < 0.001). UBT-based model showed moderate diagnostic strength in Hp-GCS (AUC = 0.78, 95% CI 0.74–0.82), better than UBT alone (p < 0.001). The sensitivity and specificity of UBT-based index were 80.2% and 61.9% at optimal cutoff in training setting, comparable in validation setting, which sensitivity and specificity were 76.9% and 59.6%. Number needed to screen was decreased along with older age, as well as stronger positivity of UBT. The optimal cost-effective Hp-GCS protocol with detection rate (DR = 77.9%) was endoscopic screening in age 40–59 years and positive UBT, or age ≥60 years without UBT. Incremental analysis suggested a preferable protocol as endoscopic screening in age ≥40 years without UBT (DR = 93.3%). UBT had moderate diagnostic strength in massive gastric cancer screening, and might be cost-effective in middle-aged population (40–59 years). More robust Hp-GCS protocol needs further investigate in test methods and individual biologic features.